Genocide in Libya - Ahmida, Ali Abdullatif, 1953- author.
1 online resource (xix, 213 pages)
Keywords: "This original research on the forgotten Libyan genocide, specificially recovers the hidden history of the fascist Italian concentration camps (1929-1934) through the oral testimonies of Libyan survivors. This book links the Libyan genocide through cross-cultural and comparative readings to the colonial roots of the Holocaust and genocide studies. Between 1929 and 1934, thousand of Libyans lost their lives, directly murdered and fell victims to Italian deportations and internments. They were forcibly removed from their homes, marched across vast tracks of deserts and mountains, and confined behind barbed wire in 16 concentration camps. It is a story that Libyans have recorded in their Arabic oral history and narratives while remaining hidden and unexplored in a systematic fashion, and never in the manner that has allowed us to comprehend and begin to understand the extent of their existence. Based on the survivors' testimonies, which took over ten years of fieldwork and research to document, this new and original history of the genocide is a key resource for readers interested in genocide and holocaust studies, colonial and post-colonial studies and African and Middle Eastern studies"--